Ent-kaurane diterpenoids from the Annonaceae family: a review of research progress and call for further research - Ibrahim, Traore S.; Khongorzul, Purevdulam; Muyaba, Moses; Alolga, Raphael N. (Frontiers in Pharmacology, 2023)
The Annonaceae is one of the plant families with members that are credited with numerous pharmacological functions. Among the group of compounds responsible for these bioactivities are the ent-kaurane diterpenoids. The ent-kauranes are a group of 20-Carbon, tetracyclic diterpenoids that are widely distributed in other plant families including the Annonaceae family. This minireview focuses mainly on the ent-kaurane diterpenoids isolated from the Annonaceae family, delineates the various biological activities of these compounds, and highlights the research gaps that exist for further scientific scrutiny.